DISASTER MITIGATION LITERACY PROFILE OF HIGH SCHOOL STUDENTS IN PONTIANAK - Minderman, Nasreen Nischka; Afandi; Tenriawaru, Andi Besse (Jurnal Pelita Pendidikan, 2025)
Understanding disaster mitigation is needed to reduce risk and respond more effectively to disasters. This study aimed to analyze the disaster mitigation literacy profile of high school students in Pontianak. This research used a quantitative descriptive method. The research subjects involved grade XI high school students in Pontianak, with as many as 331 respondents. The instrument in this study used a questionnaire containing a list of statements arranged according to a Likert scale. The results indicated that the disaster mitigation literacy of high school students in Pontianak included the criteria of “tough” in all components and indicators showed by the average percentage score of the knowledge component is 75.55%, the attitude component is 77.47%, and the skills component is 74.36%. The results of disaster mitigation literacy of high school students in Pontianak based on gender and disaster experience are also included in the “tough ” criteria. Therefore, the study results show that the disaster mitigation literacy of high school students in Pontianak is in the “tough” criteria.